Legal cartography of digital informative self-determination: a jurisprudential construction right - Caballero Trenado, Laura (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2021)
The architecture of the right to informative self-determination, in its digital aspect, is shaped by jurisprudential doctrine. Fasting of its own regulation until the entry into force of the General Data Protection Regulation, on May 25, 2018, digital informational self-determination has been conformed to the chisel of three jurisdictional bodies (the Court of Justice of the European Union, the Constitutional Court and the Supreme Court) that have been shaping and defining their content and scope. The evolution of this right since its recognition by the CJEU in its well-known Decision of May 13, 2014 is very relevant. Currently, a search on the Internet with two surnames is sufficient to recognize this right if it damages the honor, personal or family privacy or the image of its holder. This has been endorsed by the Supreme Court in STS 16244/2020, of November 27. This article addresses the most relevant jurisprudential milestones in order to sketch a current legal cartography of the right to informative self-determination.